Disproportionation of nitrogen induced by DC plasma-driven electrolysis in a nitrogen atmosphere. Issue 18 (31st August 2022) - Pattyn, C.; Maira, N.; Buddhadasa, M.; Vervloessem, E.; Iseni, S.; Roy, N. C.; Remy, A.; Delplancke, M.-P.; De Geyter, N.; Reniers, F.
Abstract : A simultaneous oxidation and reduction of nitrogen is performed for nitrogen fixation with a DC plasma-electrolysis operated in N2 . Abstract : Nitrogen disproportionation i.e. its simultaneous conversion to compounds of higher (NO x ) and lower (NH3 ) oxidation states in a N2 DC plasma-driven electrolysis process with a plasma cathode is investigated. This type of plasma–liquid interaction exhibits a growing interest for many applications, in particular nitrogen fixation where it represents a green alternative to the Haber–Bosch process. Optical emission spectroscopy, FTIR and electrochemical sensing systems are used to characterize the gas phase physico–chemistry while the liquid phase is analyzed via ionic chromatography and colorimetric assays. Experiments suggest that lowering the discharge current enhances nitrogen reduction and facilitates the transfer of nitrogen compounds to the liquid phase. Large amounts of water vapor appear to impact the gas discharge physico–chemistry and to favor the vibrational excitation of N2, a key parameter for an energy-efficient nitrogen fixation.